Analisis Keputusan Pembelian Konsumen dengan Kualitas Produk dan Kualitas Pelayanan pada Roti Domora Fresh Tanjung Morawa - Ayu wulandari; Muhammad Hilman Fikri (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This study aims to determine the effect of product quality and service quality at the Domora Fresh bakery, Tanjung Morawa. The sample of this research is consumers who buy at the research object as many as 91 consumers. By using the SPSS analysis tool while the analysis technique used is multiple regression analysis, t test, F test and the coefficient of determination. The suitability test using the t test was carried out to test the effect partially between the independent variables and the dependent variable with the assumption that other variables are considered constant. The results of the study show that the quality of products and services influences the purchasing decision of the object of research. It is also seen that the two dependent variables have a big role in increasing consumer purchasing decisions.